2011
DOI: 10.1007/s12301-011-0008-0
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the fragility of renal calculi in response to shock wave lithotripsy through their radiographic appearance

Abstract: Objectives: To evaluate the radiological characteristics of renal stones on plain X-ray film of the kidneys, ureters and bladder (KUB) area as predictors of stone fragility during shock wave lithotripsy (SWL). Patients and Methods: This prospective study included 336 patients who had a single renal pelvic stone £20 mm and were managed by SWL at 3 different centers. The patients were classified according to the radiological appearance of the stone on KUB film in terms of homogeneity, smoothness of the outline, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…However, a study conducted by Bhatta et al (1989) and later confirmed by Elkoushy et al (2011) reported that cystine stones with rough morphology were more susceptible to SWL than those with smooth morphology. URS is also used for patients with stones in the upper urinary tract.…”
Section: Surgical Interventionmentioning
confidence: 97%
“…However, a study conducted by Bhatta et al (1989) and later confirmed by Elkoushy et al (2011) reported that cystine stones with rough morphology were more susceptible to SWL than those with smooth morphology. URS is also used for patients with stones in the upper urinary tract.…”
Section: Surgical Interventionmentioning
confidence: 97%